Characterization of Two Ethephon-Induced IDA-Like Genes from Mango, and Elucidation of Their Involvement in Regulating Organ Abscission - Rai, Avinash Chandra (Genes (Basel), 2021)
In mango (Mangifera indica L.), fruitlet abscission limits productivity. The INFLORESCENCE DEFICIENT IN ABSCISSION (IDA) peptide acts as a key component controlling abscission events in Arabidopsis. IDA-like peptides may assume similar roles in fruit trees. In this study, we isolated two mango IDA-like encoding-genes, MiIDA1 and MiIDA2. We used mango fruitlet-bearing explants and fruitlet-bearing trees, in which fruitlets abscission was induced using ethephon. We monitored the expression profiles of the two MiIDA-like genes in control and treated fruitlet abscission zones (AZs). In both systems, qRT-PCR showed that, within 24 h, both MiIDA-like genes were induced by ethephon, and that changes in their expression profiles were associated with upregulation of different ethylene signaling-related and cell-wall modifying genes. Furthermore, ectopic expression of both genes in Arabidopsis promoted floral-organ abscission, and was accompanied by an early increase in the cytosolic pH of floral AZ cells—a phenomenon known to be linked with abscission, and by activation of cell separation in vestigial AZs. Finally, overexpression of both genes in an Atida mutant restored its abscission ability. Our results suggest roles for MiIDA1 and MiIDA2 in affecting mango fruitlet abscission. Based on our results, we propose new possible modes of action for IDA-like proteins in regulating organ abscission.